A climate of public readiness: climate adaptation action - Beery, Thomas H.; Bergstrom, Ryan D. (Frontiers in Climate, 2025)
The discourse surrounding climate change and the adaptation solutions needed to mitigate its impacts is often framed in terms of future time horizons. However, it has become increasingly clear that impacts are occurring today, so public awareness and engagement are critical. Despite the growing recognition of the worsening climate crisis, the gap between public understanding and approval of adaptation strategies remains a significant obstacle to community resilience in many locations. One country where broad-based public support for climate adaptation is emerging is Sweden, and one region within Sweden that is acutely experiencing the immediate impacts of climate change is Skåne. This perspective highlights a critical opportunity for decision-makers in southern Sweden to capitalize on public support to implement adaptation solutions now. While doing so, we argue that while climate adaptation may look different elsewhere, the combination of historical vulnerabilities, climate threats, public support, and governance structures is universal. Thus, the lessons learned in southern Sweden are generalizable to other similar contexts.